ANALISIS SCAFFOLDING PADA TAHAP PELAKSANAAN PENGECORAN STRUKTUR HOPPER DENGAN METODE ELEMEN HINGGA - Tarigan, Valentana Ardian; Laia, Fiber (Universitas Quality, 2023)
The use of scaffolding as a tool in the implementation of concrete casting in reinforced concrete structure buildings requires precise analysis and calculations so that in the implementation it can avoid failures in the implementation of structures and in preventing work accidents that can result in fatalities. Determination of the dimensions of the scaffolding that are safe on the structure, the right scaffolding model for safe implementation and knowing the location of the large stress on the scaffolding. The research method is carried out by adjusting the data to the dimensions of the Hopper structure, the parameters used according to the loading regulations and the analysis of the structure. Standard scaffolding used in the field module 1.2 m x 1.2 m is safe against design loading. The use of double bracing is highly recommended and the pipe size used is 76 mm in diameter.